Information Technology Moderates The Effect Of Human Resource Management Audit And Work Motivation On Employee Performance - Fifi Selvi; Haliah Haliah; Nirwana Nirwana; Muh Alief Fahdal Imran; Hasnawiyah Hasan (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to examine the effect of human resource management audits and work motivation on employee performance with information technology as a moderating variable. This research is a quantitative study with a qualitative associative approach. This research was conducted at PT Bumi Karsa. This study used a purposive sampling method with a total of 62 respondents. The method of data collection was using a questionnaire which was distributed via via google form. The data used in this study is primary data collected through a questionnaire survey. Data analysis uses multiple regression analysis to determine the effect of human resource management audit and work motivation. While the moderation test uses Moderate Regression Analysis (MRA) or interaction test. The results of this study indicate that the human resource management audit and work motivation have a significant positive effect on employee performance. Information technology can moderate work motivation on employee performance, while information technology cannot moderate human resource management audits on employee performance.